2010
DOI: 10.1111/j.1749-4486.2010.02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Oromandibular dystonia questionnaire (OMDQ‐25): a valid and reliable instrument for measuring health‐related quality of life

Abstract: The Oromandibular Dystonia Questionnaire (OMDQ-25) is the first reliable and valid instrument to measure health-related quality of life in patients with oromandibular dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Subscales reported. Distribution of individual data given Low grade: Children in cohort and not reported separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subscales reported. Distribution of individual data given Low grade: Children in cohort and not reported separately.…”
Section: Methodsmentioning
confidence: 99%
“…Six studies attempted to validate the Glasgow Benefit Inventory against another patient-recorded outcome measure. 34,35,46,54,121,127 Five of these compared with another patient-recorded outcome measure 35,46,54,121,127 (Fairley Nasal Questionnaire (FNQ), Blepharospasm Disability Index (BDSI), HUI 3, OMDQ 25). In only one paper was there an attempt to compare the Glasgow Benefit Inventory with a patient-recorded outcome measure Hearing Disability and Handicap Scale (HDHS) and objective testing of hearing outcomes.…”
Section: Validating Case Seriesmentioning
confidence: 99%
“…Thirty scales have been assessed for evaluation of different types of dystonia ( [7,42]; [6,10,39,66]; [17,24,38,52,63,64,68,74,79,93,[105][106][107]) ( Table 3). Seven of them, the Blepharospasm Disability Index (BDI), the Cervical Dystonia Impact Scale, the Toronto Western Spasmodic Torticollis Rating Scale, the Craniocervical Dystonia Questionnaire (CDIS), the Voice Handicap Index (VHI), the Vocal Performance Questionnaire (VPQ) and the Fahn-Marsden Dystonia Rating Scale (FMDRS), reached the recommendation status [2] (Table 4).…”
Section: Dystoniamentioning
confidence: 99%
“…The Movement Disorders Society Task Force on dystonia rating scales suggested that Oromandibular Dystonias Questionnaire (OMDQ-25) still needs further assessment to be validated and recommended [75]. However, the OMDQ-25 is clinimetrically valid, reliable, and sensitive to change in evaluating psychosocial and health-related change and improvement in OMDy [22]. Generalized dystonia rating scales, such as Burke-Fahn-Marsden Scale and the Unified Dystonia Ranking Scale, include orofacial subcomponents that can be useful in assessing the severity of the OMDy, guiding the treatment, and assessing the clinical response [29] ( Table 2).…”
Section: Evaluation Of Treatment Outcomementioning
confidence: 99%